2021
DOI: 10.1128/mcb.00648-20
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Lamin A/C Expression Is a Key Determinant of Paclitaxel Sensitivity

Abstract: Paclitaxel is a key member of the Taxane (Taxol/paclitaxel, docetaxel/taxotere) family of successful drugs used in the current treatment of several solid tumors, including ovarian cancer. The molecular target of Taxol/paclitaxel has been identified as tubulin, and paclitaxel binding alters the dynamics and thus stabilizes microtubule bundles. Traditionally, the anti-cancer mechanism of paclitaxel has been thought to originate from its interfering with the role of microtubules in mitosis, resulting in mitotic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Do MTD act by targeting dividing cancer cells and the dying cells in turn induce an environmental change leading to the destruction of neighboring cancer cells, a so-called bystander effect, which would allow to target more tumor cells ( Mitchison, 2012 )? Do these drugs perturb other MT functions, especially in interphase ( Wang et al, 1998 ; Giannakakou et al, 2000 ; Stone and Chambers, 2000 ; Ogden et al, 2014 ; Mitchison et al, 2017 ; Smith et al, 2021 )?…”
Section: Introductionmentioning
confidence: 99%
“…Do MTD act by targeting dividing cancer cells and the dying cells in turn induce an environmental change leading to the destruction of neighboring cancer cells, a so-called bystander effect, which would allow to target more tumor cells ( Mitchison, 2012 )? Do these drugs perturb other MT functions, especially in interphase ( Wang et al, 1998 ; Giannakakou et al, 2000 ; Stone and Chambers, 2000 ; Ogden et al, 2014 ; Mitchison et al, 2017 ; Smith et al, 2021 )?…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown resistance to paclitaxel-induced nuclear breakage in lamin A/C over-expressing cancer cells. It was found that decreased nuclear lamin A/C protein levels correlate with nuclear shape deformation and are a critical predictor of cancer cells’ susceptibility to paclitaxel(95). We have encountered different players of similar processes being significantly affected by the abundance or deficiency of lamin A.…”
Section: Discussionmentioning
confidence: 99%
“…This finding provides a new addition to the well-accepted notion that paclitaxel acts as a mitotic inhibitor. Thus, in addition to proliferation, a malleable nuclear envelope caused by a defective nuclear envelope structural proteins ( 69 a) provides another specificity of cancer cells for killing by paclitaxel, as non-neoplastic cells have a sturdier nuclear envelope and are more resistant to paclitaxel-induced breaking ( 59 , 68 ).…”
Section: Non-mitotic Mechanisms Of Paclitaxel In Inducing Micronuclea...mentioning
confidence: 99%
“…With the realization of the non-mitotic mechanism of paclitaxel in killing cancer cells ( 68 ), a new rationale may motivate the study of adding CDK4/6i to paclitaxel regimen, especially to the dose dense treatment of metastatic breast and recurrent ovarian cancer ( Figure 3 ). Furthermore, ongoing study will yield additional understanding of the potential mechanism(s) of CDK4/6 inhibition in damaging cancer cells, in addition to the cytostatic effects.…”
Section: Combination Therapy: Rationale For Synergy Between Paclitaxe...mentioning
confidence: 99%